2020
DOI: 10.1055/s-0040-1717126
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA Damage and Serum Levels of Copper, Zinc, and Selenium in Full-Term Neonates with Late-Onset Sepsis

Abstract: Objective The alteration in certain trace elements is usually associated with impaired immune function and higher oxidative stress. Therefore, these elements are suggested to play an important role in the pathogenesis of neonatal sepsis. We aimed to evaluate copper (Cu), zinc (Zn), and selenium (Se) serum levels in full-term neonates with late-onset sepsis (LOS) and correlate these levels with DNA damage and other risk factors of sepsis. Methods The study included a group of 100 neonates diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In this study, we used the alkaline version of the comet assay for detection the damage of genetic material not only because of oxidative stress but also to assess the total genotoxic pressure in severe COVID-19 patients. Our results are consistent with previously published data on DNA damage in severely ill patients with multiple trauma [ 21 ] and sepsis [ 40 ], in which the level of multiple organic dysfunctions has been shown to positively correlated with DNA damage. Similar, Pinto concluded that SARS-CoV-2 virus could promote mutagenesis by increasing in micronuclei-bearing cells in buccal mucosa of 11 patients with COVID-19 [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we used the alkaline version of the comet assay for detection the damage of genetic material not only because of oxidative stress but also to assess the total genotoxic pressure in severe COVID-19 patients. Our results are consistent with previously published data on DNA damage in severely ill patients with multiple trauma [ 21 ] and sepsis [ 40 ], in which the level of multiple organic dysfunctions has been shown to positively correlated with DNA damage. Similar, Pinto concluded that SARS-CoV-2 virus could promote mutagenesis by increasing in micronuclei-bearing cells in buccal mucosa of 11 patients with COVID-19 [ 41 ].…”
Section: Discussionsupporting
confidence: 93%